2006
DOI: 10.1016/j.rmed.2006.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin versus levofloxacin against acute exacerbations of chronic bronchitis: The Latin American Cohort

Abstract: We compared the efficacy and safety of moxifloxacin and levofloxacin for the treatment of patients with acute exacerbations of chronic bronchitis (AECB) using a prospective, randomized, double blind, parallel-group clinical trial design. A total of 563 patients with AECB were enrolled (437 efficacy-valid) at 34 centers in Mexico, Argentina, Brazil, Colombia, and Peru. Patients were randomized to oral therapy with either moxifloxacin 400 mg once daily for 5 days or levofloxacin 500 mg once daily for 7 days. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
(15 reference statements)
0
17
0
Order By: Relevance
“…Unless specified, most of the medications described in the following studies were administered orally. Table 1 presents comparative studies of short-course fluoroquinolone treatment and standard therapy (≥7 days) of anti micro bial agents on clinical and bacteriological outcomes in patients with AECB [7,[26][27][28][29][30][31][32][33][34][35][37][38][39][40][41][42][43][44].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unless specified, most of the medications described in the following studies were administered orally. Table 1 presents comparative studies of short-course fluoroquinolone treatment and standard therapy (≥7 days) of anti micro bial agents on clinical and bacteriological outcomes in patients with AECB [7,[26][27][28][29][30][31][32][33][34][35][37][38][39][40][41][42][43][44].…”
Section: Search Resultsmentioning
confidence: 99%
“…Bacteriological eradication rate was also similar in the two treatment groups: 92.8 and 93.8% in the moxifloxacin and levofloxacin groups, respectively. The authors suggested that short-course, once-daily moxifloxacin therapy has compliance advantages over other currently used therapies [40].…”
Section: Reviewmentioning
confidence: 99%
“…A study that compared moxifloxacin (400 mg/day for 5 days) to levofloxacin (500 mg/day for 7 days) in a cohort from Latin America with AECB reported equivalent efficacy for both therapies (clinical success 91 vs 94%, respectively) [49]. In this study, the average age was 59 ± 15 years for the moxifloxacin group and 61 ± 15 years for the levofloxacin group.…”
Section: Category Antibiotic Recommendationmentioning
confidence: 57%
“…This result is compatible with that of a previous study comparing moxifloxacin with levofloxacin. 20 Our study has some limitations. As this was an investigator initiated academic project a double-blind study could not be conducted due to financial constraints and logistic problems.…”
Section: Discussionmentioning
confidence: 89%